2012
DOI: 10.12693/aphyspola.122.557
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Structural Properties of High Purity Al Processed by ECAP

Abstract: The mechanical properties and substructure formation of high purity aluminium (99.999%) processed by severe plastic deformation method (equal channel angular pressing) were studied. The equal channel angular pressing process was carried out at room temperature by route C (sample rotation around the axis about 180• after each pass) in a die with two channels intersecting at an angle of Φ = 90. The softening mechanism through dynamic recovery was recognized up to 6th equal channel angular pressing pass, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…8 the hardness increases by aproximately a factor of two after 2 passes and thereafter the microhardenss continues to rise but to a smaller amounts. These trends are generally consistent with earlier data where the hardness measurements were taken on X plane [11,17,18]. Earlier studies demonstrated there is a good correlation between the values recorded in microhardness measurements and the internal microstructures within the material [19][20][21].…”
Section: Fig7 Vickers Micro-hardness Vs Ecap Passessupporting
confidence: 91%
See 2 more Smart Citations
“…8 the hardness increases by aproximately a factor of two after 2 passes and thereafter the microhardenss continues to rise but to a smaller amounts. These trends are generally consistent with earlier data where the hardness measurements were taken on X plane [11,17,18]. Earlier studies demonstrated there is a good correlation between the values recorded in microhardness measurements and the internal microstructures within the material [19][20][21].…”
Section: Fig7 Vickers Micro-hardness Vs Ecap Passessupporting
confidence: 91%
“…Thus, by taking measurements along linear traverses it is possible to obtain quantitative information on the variations of hardness and homogeneity on selected planes of sectioning after ECAP. In the last decades several studies focused on the mechanical behavior and the microstructural evolution of pure Al and Al alloys processed by ECAP [6][7][8][9][10][11][12][13][14][15]. However, very little information is available at present on the evolution of microhardness and on degree of homogeneity existing along the orthogonal and longitudinal axes of billets processed by ECAP [17,18], although this information is important if the pressed billets will be used in industrial application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring the microhardness (HV) along linear traverses on the sample, it is possible to obtain quantitative information on the variations in the hardness and homogeneity on selected planes. In the last decades, several studies focused their examination on the mechanical behavior and the microstructural evolution of pure Al and Al-alloys processed by ECAP [13][14][15][16][17]. However, very little information is available about the evolution of microhardness and the degree of homogeneity along the orthogonal and longitudinal axes of billets processed by ECAP [16], although this information is crucial for the industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The small punch test (SPT) method was applied in the study of pure aluminium after severe plastic deformation by equal channel angular pressing (ECAP). SPT is using miniature discs specimens of 8 mm in diameter and 0.5 mm thickness [1] and can be used for determining various mechanical properties from very small volume of materials: creep [2][3][4][5][6], static [7][8][9][10][11][12][13][14][15][16] and fracture [17][18][19][20][21]. In these tests, a small punch with a spherical head penetrates through the disc specimen into a receiving hole.…”
Section: Introductionmentioning
confidence: 99%